Nâng cao tính thống nhất giữa giáo dục nhà trường, gia đình và xã hội trong điều kiện mới - Võ, Tấn Quang (Bộ Giáo dục và Đào tạo, 2013)
The integration of schooling educationeducation in family and social education is a scientific subject at mistrial level. In this article, the author proposes four strategies in order to improve this integra tion under the condition of market mechanism, democratisation of social activities and development of international relationship.